Understanding the immovable property data in Malaysia and the challenges for data sharing - M. Ali, Safina; Suratman, Robiah; M. Othman, Razib; Mohammad, Mohammad Tahir Sabit (Faculty of Built Environment and Survey, UTM, Johor Malaysia, 2019)
In Malaysia, distribution of estate happens after a person’s death. To distribute the deceased estate, the beneficiaries need to submit an application with the latest status of deceased property information and list of legal beneficiaries entitled to the estate. The estate information is decentralized stored and beneficiaries need to obtain the status of the property at each of the property agencies. Besides that, the legal beneficiary’s information should be available to facilitate the distribution of property. It takes time and costly. This requires an integrated property information system to expedite the process of searching the deceased property simultaneously as well as assisting in the distribution of the estate. The objective of this paper is to understand the process flow of the estate distribution as well as the related property agencies related to estate distribution. Furthermore, it is necessary to identify the constraints in estate distribution management and to develop a data model of the property. This study only covered the immovable property for Muslim. The preliminary study was undertaken to investigate the estate distribution process including the property agencies, the jurisdiction, and the property system. An interview was conducted with the related agencies to the estate agencies and the distribution of the estate. A workflow diagram is used to depict the pre-application process of estate distribution. The entity relationship diagrams illustrate the relationship between the different types of properties. Others than that, the constraints and challenges also be determined.